Monitoring of gene expression proWles and identiWcation of candidate genes involved in drought responses in Festuca mairei - Wang, J.P.; Bughrara, S.S.
To understand the molecular genetic basis underlying drought tolerance in grasses, the cDNAampliWed fragment length polymorphism (cDNAAFLP)technique was applied for identiWcation of genes responding to drought stress in a xerophytic adapted plant, Festuca mairei. A total of 11,346 transcript derived fragments (TDFs)were detected, and 464 (4.1